Integrasi Agama dan Sains dalam Tafsir Ilmi Kementerian Agama RI - Faizin Faizin (Jurnal Ushuluddin, 2017)
The application of religious and scientific integration in the Tafsir Ilmi of Ministry of Religious Affairs was critically analyzed in this paper. The paradigm of religious and scientific integration was used in order to expose the building framework of the integration. Three forms of the integration paradigm were highlighted, namely: [1] scientific interpretation as one of the patterns of integration of religion and science, [2] theology as the basis of the integration, and [3] Tafsir Ilmi as an effort to present ethical values. The result of the study showed that Tafsir Ilmi was the one which was deductive-confirmatively implemented in the integration of religion and science. The pattern of religious and scientific integration had included theology as its basis in the Tafsir Ilmi, in which the theological side became central fusion of the Qur’anic text and the universe through the reading of tafsir and science. Metaphysical side was presented in order to bring the majesty of Allah SWT. The values of monotheism, science, and caliphs had an integral relationship and became instruments for the birth of the ethical values. Theological aspects and ethics looked thickly decorated in the pages of the Ilmi interpretation